Public knowledge of early stroke symptoms in the Vilnius region - A. Atkočiūnas; M. Mačionytė; R. Mameniškienė (Neurologijos seminarai)
Background and aim. Stroke remains one of the most common causes of death and disability in the world. The evident decline in disabling outcomes can be attributed to the increasing use of reperfusion therapies. Stroke recognition and urgent admission of patients to specialized stroke centres after the onset of first stroke symptoms are essential for treatment outcomes. This study aims to assess public stroke awareness and its change since 2019. Methods. An anonymous cross-sectional study involving 300 Vilnius residents was conducted in 2022, the results of which were compared with the data of 502 respondents in 2019. A closed-ended questionnaire was used for the study. Statistical analysis was performed using IBM SPSS software with p<0.05 significance level. Results. Stroke was identified as an acute cerebrovascular disorder by 83.3% of respondents in 2022 (82.7% in 2019). At least one correct warning sign of stroke was indicated by 98.7% of respondents (96.4% in 2019). The most commonly mentioned symptoms of stroke were one-sided face, arm or leg sensory disturbances, paralysis, or weakness (90.0%) and speech disorder (83.3%), with 82.1% and 81.5% respectively in 2019. Only 58% (45.4% in 2019) of respondents reported visual impairment as a stroke symptom. Women had better knowledge of stroke than men (p<0.05). The internet was the main source of information for 63.3% of respondents (64.9% in 2019). Conclusions. Since 2019, stroke awareness has improved in Vilnius. This proves that F.A.S.T. campaign has reached the public. Women have better knowledge of stroke than men. Visual impairment is the least known symptom of stroke. Therefore, the search for new information programmes, especially directed to the targeted audience, can be useful for better publicity.